NUTRITION IN ADULT CRITICALLY ILL PATIENTS - Palibrk, Ivan; Djukanovic, Marija; Stefanovic, Dona (Medical Research, 2024)
Nutrition is a crucial component of critically ill patients’ treatment. The questions to be answered are when to start with nutrition therapy, as well as to determine the optimal route and the amounts of macro and micronutrients to apply and how to define the amount of energy to provide.Critical illness has its three phases: Early period (previously  ebb phase) for a period of 1-2 days; Late period (previously flow phase) for a period of 3-7 days; Late phase (Phase Rehabilitation or Chronic Phase). Every of above mentioned phases has its characteristics. During the first phase severe catabolism is increased, which is during the next 3 to 4 days gradually proceeding to the anabolism. The recommendations for critically ill patients’ nutrition were formed based on these phases.Early nutrition therapy, especially early parenteral nutrition with high energy and protein intake should be avoided in first three days of critical illness. Reaching the nutritional goal should be initiated only after 3 to 4 days from the onset of critical illness. According to ESPEN recommendations, daily calorie intake should be initiated at 20-25 kcal/kg/day, while daily protein intake at 0,8g/kg/day with a gradual increase to 1,3 g/kg/day. On the other hand, ASPEN recommends 12-25kcal/kg/day of daily calorie intake with daily protein intake at 1,2-2 g/kg/day. The optimal route of feeding is enteral whenever possible. Alternatively, parenteral route should be used. Indirect calorimetry serves as a basis for determining nutritional needs in critically ill patients.Conclusion: Nutritional therapy is essential for critically ill patients. Nutrition should be obtained through enteral route whenever possible. Energy and protein intake should be gradually introduced in critically ill patients’ treatment. Nutritional therapy prescription should be adapted to the patients’ needs.
Keywords: Critically Ill; Enteral; Intensive care; Nutrition; Parenteral